Immigrants, Household Production and Women's Retirement - Giovanni Peri; Agnese Romiti; Mariacristina Rossi (Institute for the Study of Labor (IZA), 2013)
Women contribute disproportionately to household production, especially in Southern European countries. As a consequence of population aging assistance to elderly parents, rather than child care, has become a prevalent activity in home-production services. Immigrant labor has increasingly become a substitute for women labor in those services. Their presence, therefore, may allow women over 55 to work more outside of the house and retire later. We use a unique database of Italian households to identify the effect of local availability of foreign workers on planned retirement age and labor supply of Italian women. We find that an exogenous increase by one point in the immigrant percentage of the local population increased the planned retirement age of women over 55 by two months relative to similar men. For women with old parents the increase was four months and if they were in low-wealth households the increase was one full year. The same inflow of immigrants also increased the probability that women over 55 work outside the home by nine percentage points, relative to men.
Keywords: J22; J26; F22; 330; international migration; retirement; labor supply; home production; elderly care